Comparison of short-term efficacy of two bipolar radiofrequency ablation forceps for rheumatic heart disease concomitant with atrial fibrillation - Zhang, Ning; Hou, Ming; Mei, Bo; Liu, Yong; Lai, Ying-long (Frontiers in Cardiovascular Medicine, 2024)
Background Currently, the bipolar radiofrequency ablation forceps manufactured by AtriCure are the main instrument for surgical ablation in patients with rheumatic heart disease (RHD) concomitant with atrial fibrillation (AF). The bipolar radiofrequency ablation forceps by Med-Zenith has a greater advantage in price compared with AtriCure. However, few studies have been reported on the comparison of their clinical efficacy. The aim of this study is to compare the short-term clinical efficacy of the two ablation forceps for RHD concomitant with AF. Methods Clinical data of 167 patients with RHD concomitant with AF admitted to the Department of Cardiac Major Vascular Surgery, Affiliated Hospital of North Sichuan Medical College, were retrospectively analyzed, and the restoration efficacy of sinus rhythm (SR) and cardiac function after surgery were compared with two ablation forceps. Results The end-systolic diameter of the right atrium and the end-systolic diameter of the left atrium in the patients of both groups at each postoperative time point decreased compared with that of the preoperative period (P < 0.05), and the left ventricular ejection fraction started to improve significantly at 6 months after surgery compared with that of the preoperative period (P < 0.05). There was no difference between the two groups of patients in the comparison of the aforementioned indicators at different points in time (P > 0.05). At 12 months postoperatively, the SR maintenance rate in using the ablation forceps by Med-Zenith (73.3%) was lower than that for AtriCure (86.4%) and the cumulative recurrence rate of AF in using the Med-Zenith ablation forceps was greater than that for AtriCure. Conclusions The two bipolar radiofrequency ablation forceps compared in the study are safe and effective in treating patients of RHD concomitant with AF, and the ablation forceps by AtriCure may be more effective in restoring SR in the short term.